Role of Artificial Intelligence in Determining Ideal Nasal Tip Projection in Diverse Populations - Aaron L. Wiegmann, MD, MS; Elizabeth S. O’Neill, MD; Stephanie L. Taiberg, BS; Sammy Sinno, MD; Rod J. Rohrich, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Nasal tip projection ideals have been based on the Caucasian nose; however, many racial groups have underprojected tips. Several methodologies have been described to measure ideal nasal tip projection. This study aimed to compare various methods to racially diverse groups to elucidate those best suited for race-specific facial morphology. Methods:. An openly accessible artificial intelligence image generator was used to generate images of Caucasian, Middle Eastern, and African American noses. Tip projection was manually measured using 5 different ideal tip projection methods. One-way analysis of variance with post hoc Tukey honest significant difference test evaluated differences between racial cohorts. One-sample t tests were used for comparisons to previously described aesthetic ideals, and a P value of less than 0.05 was considered statistically significant. Results:. Twenty lateral images were analyzed per racial cohort (10 men and 10 women). All racial groups—except for male Middle Eastern noses (P = 0.01)—were measured as ideal using the Byrd nasal length proportion method. Caucasian and Middle Eastern noses measured ideal using the nasolabial tip projection method. African American female noses measured ideal using the nasofacial tip projection method. Only Caucasian noses were ideal using the lip tangent method. Conclusions:. This study suggests that the ideal nasal length to tip length ratio of two-thirds (67%) has generalizability across these racial groups; the lip tangent is an excellent method for evaluating tip projection in Caucasians; and assessment of ideal tip projection in Middle Eastern and African American groups should use regional midface and lower face anatomy to account for differences in facial morphology.